Realization of Wafer-Scale 1T-MoS2 Film for Efficient Hydrogen Evolution Reaction - Kim, Hyeong U.; Kim, Mansu; Seok, Hyunho; Park, Kyu Young; Moon, Ji Yun; Park, Jonghwan; An, Byeong Seon; Jung, Hee Joon; Dravid, Vinayak P.; Whang, Dongmok; Lee, Jae Hyun; Kim, Taesung (ChemSusChem, 2021)
The octahedral structure of 2D molybdenum disulfide (1T-MoS2) has attracted attention as a high-efficiency and low-cost electrocatalyst for hydrogen production. However, the large-scale synthesis of 1T-MoS2 films has not been realized because of higher formation energy compared to that of the trigonal prismatic phase (2H)-MoS2. In this study, a uniform wafer-scale synthesis of the metastable 1T-MoS2 film is performed by sulfidation of the Mo metal layer using a plasma-enhanced chemical vapor deposition (PE-CVD) system. Thus, plasma-containing highly reactive ions and radicals of the sulfurization precursor enable the synthesis of 1T-MoS2 at 150 °C. Electrochemical analysis of 1T-MoS2 shows enhanced catalytic activity for the hydrogen evolution reaction (HER) compared to that of previously reported MoS2 electrocatalysts 1T-MoS2 does not transform into stable 2H-MoS2 even after 1000 cycles of HER. The proposed low-temperature synthesis approach may offer a promising solution for the facile production of various metastable-phase 2D materials.
Keywords: Electrochemical analysis; Enhanced catalytic activity; Formation energies; Large scale synthesis; Low temperature synthesis; Molybdenum disulfide; Octahedral structures; Plasma enhanced chemical vapor depositions (PE CVD); chalcogenides; chemical vapor deposition; electrocatalysis; hydrogen evolution reaction; plasma